Long-term morphological appearance of transcatheter valves left in the ascending aorta after valve dislocation during transcatheter aortic valve implantation. (14th October 2021) - Frumkin, D; Pietron, M; Kind, A; Leistner, D; Krackhardt, F; Laule, M; Brand, A; Knebel, F; Lembcke, A; Landmesser, U; Stangl, K; Dreger, H
Abstract: Background: Transcatheter valve embolization and migration (TVEM) is a potential complication of transcatheter aortic valve implantation (TAVI) (1). Registries suggest low incidence but clinical relevance due to increased acute and mid-term mortality with the majority embolizing in the aorta. However, there is little data on potential late complications such as leaflet and stent thrombosis or aortic wall alterations by migrated valves. Purpose: The aim of our study was to analyze the incidence and clinical characteristics of TVEM in a large single center cohort of TAVI patients and to examine dislocated valves by ECG-gated computed tomography (CT). Methods and results: Between July 2009 and May 2020, 40 TVEM occurred in 3387 TAVI procedures performed in our center (1.18%). TVEM was defined according to Valve Academic Research Consortium-2 (VARC-2) criteria (3). Majority of TVEM were left in the ascending aorta (31 ascending, 3 arch, 1 descending aorta). 90% of TVEM occurred with a self-expanding valve (SEV), with no difference between older and newer valve generations, 10% with a ballon-expandable valve. Analyzing a TAVI sample cohort (n=200), horizontal aorta (p<0.001, OR 11.7, 95% CI: [3.9:34.8]), defined as aortic angulation >48°(4), as well as the use of SEV (p<0.001, OR 12.8, 95% CI: [3.1:53.9]) were identified as a predisposing risk factor for TVEM. OR in SEV was severely increased when isolating the analysis for patients with horizontal aorta only (p=0.003, OR 23.75, 95% CI: [2.8:129]). No other predisposing risk factors were identified in this cohort. Out of 35 patients still alive, 6 patients were willing to participate in our imaging sub-study. CT exams were performed on average 47 months after TAVI (IQR 50 months [25%Q: 16.8, 75%Q: 72.8]). We detected no leaflet or stent thrombosis, yet CT identified pin protrusions in the aorta in 3 out of 6 patients. Conclusions: TVEM is a rare complication of TAVI. TVEM was significantly associated to the use of self-expanding valves and the presence of horizontal aorta. CT did detect pin protrusions in several cases which could bear the possible risk of perforation but showed no signs of long-term damage. FUNDunding Acknowledgement: Type of funding sources: None.